Full-scale evaluation of creep coefficients and viscoelastic moduli in honeycomb sandwich pultruded GFRP composite cross-arms: experimental and numerical study - Amir, Abd Latif; Ishak, Mohamad Ridzwan; Yidris, Noorfaizal; Mohd Zuhri, Mohamed Yusoff; Asyraf, M.R.M.; Razman, M.R.; Ramli, Z. (Elsevier, 2024)
The utilization of pultruded glass fibre-reinforced polymer composites (PGFRPC) to replace traditional wooden cross-arms in high transmission towers is a relatively recent development. While there have been numerous investigations into enhancing cross-arm structures, there remains a notable absence of research focused on the elastic characteristics of a full-scale PGFRPC cross-arm, particularly one enhanced with a honeycomb sandwich structure. To full-fill the gap, this paper presents an experimental and numerical study through cantilever beam flexural tests on assembled cross-arm condition to examine deflection behavior and the flexural creep response. For deflection behavior, the load was applied up to actual working load. For creep behavior, the hanging load was applied for 1000 h in open area condition followed ASTM D2990 standards. By using Findley’s power law, confirming the ability of this empirical approach to simulate the viscoelastic response of the cross-arm. The results obtained prove that the addition of a honeycomb sandwich structure reduced deflection and improved resilience against bending forces, enhancing specific points’ elastic modulus slightly. Long-term creep tests revealed Point Y3 had the highest strain, but the enhanced cross-arm displayed superior resistance and a shorter viscoelastic transition period, indicating increased stability. Besides that, the Findley’s Power Law Model effectively represented creep behavior for both cross-arm types, with low errors. Over 50 years, both versions showed a significant reduction in average elastic modulus, with the enhanced variant 20 % stronger due to the honeycomb structure. In conclusion, this study validates the superior creep properties of the enhanced PGFRPC cross-arm and demonstrates the honeycomb sandwich structure’s substantial role in increasing strength and extending the cross-arm’s lifespan, making it a valuable enhancement for such applications.